IMPROVING THE ABILITY OF CLASS VI STUDENTS OF SDN 08 MARUNGGI IN STORYTELLING THROUGH THE DISCUSSION METHOD - Hendi Damia Putra (LPPM Ekasakti University, 2022)
The problem studied in this study is about the implementation of learning to speak by telling stories through the discussion method with the research subject of class VI SDN 08 Marunggi in the academic year 201 9/20 20 . This study aims to (1) describe efforts to improve the ability of class VI students at SDN 08 Marunggi in telling stories through the discussion method, (2) describe the results of improving the ability of class VI students at SDN 08 Marunggi in telling stories through the discussion method. The research was conducted using the type of action research (CAR). In the analysis of research data used is qualitative data analysis. Based on the results of this study indicate that the implementation of learning with the discussion method can improve storytelling skills for grade VI students of SDN 08 Marunggi with initial observations obtained classical completeness 40%, in the first cycle increased to 60%, in the second cycle rose to 80%. In determining the assessment, 5 aspects were set to guide the assessment of each cycle, namely (1) the value of the fluency aspect of speech, (2) the value of the accuracy aspect of diction/word choice, (3) the value of the sentence structure aspect, (4) the value of the logical aspect was given, and (5) value of communicative aspect/eye contact. From these data, it can be concluded that the application of the discussion method can improve the storytelling ability of the sixth grade students of SDN 08 Marunggi.